Dental age estimation using the pulp/tooth ratio in lower canines in population of Bosnia and Herzegovina - Srabović Amila; Zukić Selma; Jesenković Džan Ahmed; Srabović Nedim (Balkan Stomatological Society, 2023)
Background/Aim:Dental age estimation in adults is a challenging process due to the lack of sufficient information on the accuracy of dental methods applied in the identification of persons without information on identity. Previous studies on dental age estimation in adults suggested that each method should be tested on a population other than one which was used to develop the specific method. The aim of this study was to estimate dental age in adults from Bosnia and Herzegovina with the radiographic analysis of the pulp/tooth ratio of lower canines and to determine differences from chronological age. Material and Methods: The sample for the research comprised 50 periapical radiographs, with visible intact lower canine teeth, derived from an archive of the Department of Dental Morphology, Dental Anthropology and Forensics. After the selection process, all radiographs were digitalized. Additional information used is the chronological age and sex of the person to whom the images belonged. The measurements of the pulp space and the lower canine tooth were performed using the ImageJ computer methods. The results of measurements were entered in formulas for assessments of dental age, as per equations given by the authors. Results: The research has shown that there is a significant difference in examined population between the dental age estimated by the analysis of pulp/tooth ratio of lower canine teeth and the chronological age. The standard error of regression for Cameriere model was 14.12 years, and this model proved to be statistically significant (p= 0.0017). Kvaal-Solheim model from 1994 has shown a standard error of 15.07 years, and did not prove to be statistically significant (p= 0.054), while another model from 1995, by the same authors, shows a standard error of 14.64 years, and it proved to be statistically significant (p= 0.011). Conclusions: It is possible to estimate dental age by means of pulp/tooth ratio. However, it is necessary to conduct further research that will include a larger number of examinees and different age groups and also consider the specificity of teeth in Bosnia - Herzegovina's population to acquire more accurate data on accuracy and reliability of those methods in this population.